Handbook of lubricants - Ash, Michael (Synapse Information Resources, 2012)
The Handbook of Lubricants is designed to function as a selection tool for deciding which is the most appropriate lubricant chemical to use in a formulation.
Title from PDF title page (viewed on Aug. 22, 2012).
Keywords: Lubrication and lubricants -- Handbooks, manuals, etc.; Lubrication and lubricants -- Trademarks.; Lubrication and lubricants industry -- Directories.; Chemicals -- Handbooks, manuals, etc.; elektronické knihy; electronic books